Green Synthesis of Gold Nanoparticles Using Bioreductors of Bilimbi Fruit Extract (Averrhoa bilimbi L.) as an Antioxidant - Triana, Aan Dimas; Taufikurohmah, Titik (Jurnal Pijar Mipa, 2024)
The rapid development of technology today affects the birth of renewable technologies such as nanotechnology. This study reports the results of synthesizing gold nanoparticles with a more environmentally friendly method (green synthesis) using bilimbi fruit extracted through the infusion process. This synthesis method approach can be widely used in biological preparation. This study aims to determine the characteristics of synthesized gold nanoparticles and their potential as antioxidants shown through IC50 intensity. UV-Vis spectrophotometer and TEM were used to analyze the quantitative formation of gold nanoparticles. The analysis used 20, 10, 5, and 2.5 ppm concentration variations. The UV-Vis spectrum characterization results showed a surface plasmon resonance (SPR) of 534-536 nm. The average diameter of the synthesized nanoparticles was 7.98 nm withΩΩ, an approximate overall particle size of 7-12 nm characterized using TEM. Antioxidant activity was carried out using 1,1-diphenyl-2-picrylhydrazyl (DPPH) silencing assay. The percent attenuation at each gold nanoparticle concentration of 20, 10, 5, and 2.5 ppm was 99.4%, 90.7%, 79.5%, and 71.9%, respectively. So, the IC50 value can be obtained at 0.514 ppm, which is included in the strong antioxidant. This shows that gold nanoparticles mediated by bilimbi fruit extract are effective antioxidant agents.